2018
DOI: 10.5586/asbp.3581
|View full text |Cite
|
Sign up to set email alerts
|

An ethnobotanical study of medicinal plants used in Zacatecas state, Mexico

Abstract: Despite the fact that Mexico has vast biocultural biodiversity, there are numerous regions where the traditional medicinal use of plants has not yet been studied. We aimed to document, analyze quantitatively, and preserve medicinal plant knowledge among local people living in over 40 communities in the state of Zacatecas. Ethnobotanical information was collected by semistructured interviews with 132 informants. Data were analyzed using standard quantitative indices such as relative frequency of citation, famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 49 publications
6
4
0
3
Order By: Relevance
“…According to Prüss-Üstün et al (2008), the ailments associated with poor sanitation are particularly correlated with poverty which account for about 10% of the global burden of disease. In agreement with the current finding, there are other works that report prevalence of gastrointestinal diseases and internal organs disorders such as Garedew and Abebe (2018) in Yeki District Southwest Ethiopia, Bussmann and Sharon (2006) in northern Peru, Cheikhyoussef et al (2011) in Namibia, Umair et al (2017) in Hafizabad district, Punjab-Pakistan and Reimers et al (2018) in Zacatecas state, Mexico.…”
Section: Parts Used and Methods Of Preparation Plant Remediessupporting
confidence: 92%
See 2 more Smart Citations
“…According to Prüss-Üstün et al (2008), the ailments associated with poor sanitation are particularly correlated with poverty which account for about 10% of the global burden of disease. In agreement with the current finding, there are other works that report prevalence of gastrointestinal diseases and internal organs disorders such as Garedew and Abebe (2018) in Yeki District Southwest Ethiopia, Bussmann and Sharon (2006) in northern Peru, Cheikhyoussef et al (2011) in Namibia, Umair et al (2017) in Hafizabad district, Punjab-Pakistan and Reimers et al (2018) in Zacatecas state, Mexico.…”
Section: Parts Used and Methods Of Preparation Plant Remediessupporting
confidence: 92%
“…Similar to our finding, reports by Giday (2007) in Bench, Meinit and Sheko, Lulekal et al (2013) in Ankober Amhara, Agize et al (2013) in Dawuro, Maryo et al (2015) in Kembata Tembaro, Regassa (2016) in West Shoa Oromo ethnic groups in Ethiopia, and in overseas, Casagrande (2002) in Tzeltal Maya, Hong et al (2015) in Maonan people China and Reimers et al (2018) in Zacatecas state Mexico, have also reported traditional use of plants for treating human ailments.…”
Section: Diversity Abundance and Habit Of Mps Reported For Human Ailmentssupporting
confidence: 92%
See 1 more Smart Citation
“…This is due to long experience and trial & error that led to discovery of e cacious taxa by the society, the accessibility of Mps, cultural acceptance, and the cost of the biomedical health care. The diversity medicinal plants inventoried in the present study conforms with other cultures in Ethiopia and overseas that used Mps to treat human ailments [31][32][33][34][35][36][37][38].…”
Section: Informant Consensus Factor (Icf)supporting
confidence: 55%
“…Para la elección de las plantas es necesario realizar un estudio previo de la diversidad vegetal del lugar así como del contexto históricocultural que lo rodea. Estudios como los de (Sauini et al, 2020) o el de (Lara Reimers et al, 2018) no parten de una lista prediseñada de especies vegetales sino que esta se configura como resultado de la propia investigación, esto implica la necesidad de una mayor interacción con los entrevistados y una recogida e identificación de cada especie, lo que alarga mucho más los tiempos.…”
Section: Materials Vegetalunclassified